MENINGKATKAN HASIL, MOTIVASI DAN AKTIVITAS BELAJAR SISWA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINIER NILAI MUTLAK SATU VARIABEL MELALUI MODEL PEMBELAJARAN THINK-PAIR-SHARE BERBASIS RME DI SMA NEGERI 1 SIGLI - Nurlatifah Nurlatifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
In the learning process, it is expected that students can be actively involved in learning activities and an increase in student learning outcomes. To achieve the learning objectives, a learning model is needed that can activate and facilitate students in understanding mathematical concepts and solving mathematical problems, including the Think, Pairs, Share (TPS) cooperative learning model based on RME. The problem in this study is whether the Think-Pair-Share learning model based on RME on the material of linear equations and inequalities absolute value of one variable can improve achievement, motivation and learning activities of students in class X MIPA-1 SMA Negeri 1 Sigli in the academic year 2021/2022. The population in this study were students of class X MIPA-1 SMA Negeri 1 Sigli in the academic year 2021/2022. Learning is carried out in 2 cycles on the material of linear equations with absolute value of one variable. The data obtained were analyzed descriptively. Based on the results of the study, there was an increase in learning outcomes, activities and learning motivation of students in class X MIPA-1 SMA Negeri 1 Sigli for the academic year 2021/2022. This can be seen from the results of the first cycle, the average student achievement, namely 72.85, has increased in the second cycle to 84.42. While the learning outcomes showed that in the first cycle of 35 students there were 14 students who completed or 40% and in the second cycle increased to 33 students who completed or 94.28%. So it can be concluded that the learning outcomes. Mathematics learning activities and learning motivation in class X MIPA-1 SMA Negeri 1 Sigli on the subject of linear equations and inequalities absolute value of one variable can be increased through RME-based TPS cooperative learning. With the suggestion that the teacher should choose the RME-based TPS cooperative learning model in the mathematics learning process, especially TPS on the material of linear equations and inequalities the absolute value of one variable to improve student learning outcomes.Keywords: Motivation, Activities, Learning Outcomes, learning model